Oceans 82 1982
DOI: 10.1109/oceans.1982.1151769
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of satellite scatterometer data and its impact on weather forecasting

Abstract: A review is presented of the need for remotely sensed marine surface wind data and its application to weather analysis and forecasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…1). The work done by Overland et al (1980), and Atlas et al (1982) clearly showed that the scatterometer system was highly successful in delineating surface weather patterns with significantly greater resolution than can possibly be achieved by in situ observational systems. A positive impact on forecast skill has been found in some cases when SASS winds are incorporated into numerical weather prediction models (see, for example, Duffy and Atlas 1986, Stoffelen and Cats, 1991, Lenzen et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…1). The work done by Overland et al (1980), and Atlas et al (1982) clearly showed that the scatterometer system was highly successful in delineating surface weather patterns with significantly greater resolution than can possibly be achieved by in situ observational systems. A positive impact on forecast skill has been found in some cases when SASS winds are incorporated into numerical weather prediction models (see, for example, Duffy and Atlas 1986, Stoffelen and Cats, 1991, Lenzen et al 1993).…”
Section: Introductionmentioning
confidence: 99%